Endoscopic support and virtual surgical planning as an alternative to repair orbital wall fractures (2020)
The reconstruction of the orbit has been carried out throughout history using different techniques. However, the persistence of high rates of complications mainly associated with the position of the eyeball and the migration of reconstruction implants have generated the need and importance of continuing to study new techniques, including with the help of technology. Virtual planning combined with endoscopic access and 3D models could decrease the number of complications associated with the aforementioned problems. For this, the aim of this observational retrospective study is to show the authors’ experience of 19 cases in different orbital fractures using endoscopic support and virtual planning as great alternative in orbital reconstruction. Within maxillofacial trauma, one of the greatest functional and aesthetic challenges for the surgeon is the orbital reconstruction, which in the event of not obtaining adequate results, can lead to aesthetic, functional and even occupational problems.1 The walls and orbital floor are commonly involved in maxillofacial trauma generated sensory problems, eye movement limitations, or changes in the position of the eyeball. The reason why one of the objectives of the treatment is the recovery of the anatomy in a matter of volume and position.2 The endoscopic approach has become important in maxillofacial reconstruction due to the direct visualization of fractures, which consequently results in a reduction in the complications associated with the surgical accesses made due to the extension.3 The loss of important anatomical references at the time of the reconstruction has hindered the processes and that is why the use of technology through the creation of software that obtains information to create images through computed tomography that imitate the contralateral orbit are also very useful.4 The main problem to be faced in orbital reconstruction surgery corresponds to recovering the orbital volume.5 Also, due to having complex, narrow anatomy and with important structures, the next problem is the proper visualization of anatomical structures and bone defects and their manipulation at the same time.6 This is why the objective of this study is to show our experience with 19 cases using endoscopic support and virtual planning for the management of traumatic injuries.